Single-crystal field-effect transistors based on copper phthalocyanine - Zeis, Roswitha; Siegrist, Theo; Kloc, Christian (Applied Physics Letters, 2005)
Copper phthalocyanine (Cu-Pc) single crystals were grown by physical vapor transport and field-effect transistors (FETs) on the surface of these crystals were prepared. These FETs function as p -channel accumulation-mode devices. Charge carrier mobilities of up to 1 cm2V s combined with a low field-effect threshold were obtained. These remarkable FET characteristics, along with the highly stable chemical nature of Cu-Pc, make it an attractive candidate for device applications. © 2005 American Institute of Physics.
Created from Fastlane, Scopus look-up